Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan dengan Loyalitas Sebagai Moderasi - Muhamad Ilham Faozi,; Merry Fithriani,; John Sihar Manurung,; Septa Intiar,; Desty Hapsari Kirana, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
In attracting consumers, business owners try their best to provide everything they can to meet customer satisfaction. Consumer satisfaction is a very important factor to ensure the survival of a company. The goal of a company is to create and retain consumers. In order for a company to develop and get satisfaction from consumers, a company must be able to provide more value to the quality provided to consumers. This research aims to determine the effect of product quality and service quality on customer satisfaction with loyalty as moderation. The current analysis uses a quantitative approach. The population of this research is consumers or customers who have shopped. Samples were taken from this population, and the sample selection for this study was determined by random sampling, resulting in a sample of 150 respondents. The results of this research have found that product quality and service quality influence customer satisfaction. Loyalty as a moderating variable is able to moderate the influence of product quality on customer satisfaction.